To investigate Effects of mergers and acquistions of Indian companies on performance - Shah, Khyati (2010)
ABSTRACT: In light of the recent policy changes and liberalization in Indian economy this study explores the impact of mergers and acquisitions on 8 Indian manufacturing industries over the period 1988 to 2008. Four measures of performance viz. Profit before interest and tax to sales ratio, Net Profit Ratio, Return on asset and Technical efficiency have been used to obtain the results and verify the robustness. The first three measures are derived from accounting studies and last measure calibrates changes in productivity by using Stochastic Frontier Analysis Technique. Three major estimation techniques namely least square method, Random effects model and Instrumental Variable GMM estimator have been used to obtain the results and verify robustness of results. The results indicate acquisitions are value enhancing when Technical Efficiency is used as a measure of performance. This result is consistent under all the estimation techniques. When accounting measures of performance are used merger do not have a significant impact on company profitability. This can be attributed to increasing overhead costs like research and development expenditure and advertisement expenditure of Indian industries. Mergers leading to high technical efficiency should prompt researchers to reconsider the utility of measures used to evaluate the effects of M&A. Key words: Mergers and acquisitions, Event Studies, Productivity, Stochastic Frontier Analysis, Measures of Performance.